The Vaga-Lume collection and the PNBE: an analysis of the selection criteria of the PNBE public notice and the work The mystery of the five stars (Research, Society and Development, 2020)
This article explains children's reading, its emergence in the world and in Brazil, as well as its evolution and the demand of readers in Brazilian territory, a demand that culminates with the cultural industry and in the midst of it appears the Vaga-Lume Collection . This collection was a great success with the public that was intended to serve and marked an entire generation, for years it was used in the classroom, but in the last two decades it has not been acquired by the government. The purpose of this article is to verify if the work O Mistry of the Five Stars of the Vaga-Lume collection meets the requirements stipulated by the PNBE notices for the acquisition of works that will compose the school libraries. For this we will do a documentary analysis comparing the requirements of the announcement with the book specified above, thus generating a descriptive study. The Mystery of the Five Stars by Author Marcos Rey. After analyzing and verifying each item of the three criteria proposed in the notice of 08/2011 - CGPLI, it appears that the work The Mystery of the Five Stars meets all criteria and this may have been acquired by the government to re-compose school libraries. The article leaves a suggestion of future studies for the other books by the author Marcos Rey that follow the adventures of the main characters of the analyzed story.